Epidemiology of dengue fever in Somaliland: clinical features, and serological patterns from a retrospective study - Dek Kahin Yosef; Ahmed Saeed Ismail; Barwaqo Saleban Awil; Halima Ahmed Hassan; Mohamed Ahmed Hassan (BMC Infectious Diseases)
Abstract Background Dengue fever is a significant global public health concern. However, its epidemiology in Somaliland remains poorly characterized. This study aimed to provide comprehensive data on the clinical presentation, demographic characteristics, and serological patterns of dengue fever in Somaliland. Methods A retrospective analysis was conducted on 1,410 suspected dengue cases from public hospital laboratories in Somaliland between January and September 2024. Demographic data, clinical symptoms, and results of rapid diagnostic tests for dengue NS1 antigen and IgM antibodies were analyzed. Results Of the 1,410 suspected cases, 175 (12.41%) tested positive for dengue. The majority of the patients were male (60.57%) and aged 19–38 years (45.1%). Most cases were from urban areas (58.9%). Common symptoms included fever, vomiting, nausea (86.7%), GIT problems (86.12%) were the predominant symptom of patients. Serological testing revealed 84.57% NS1 positivity, 8.57% IgM positivity, and 6.85% positivity. The peak incidence was observed in June. Only 8.67% of the patients required hospitalization. Among these 8 cases (53.3%), as sever dengue and 7 (46.6%) were dengue with warning signs. Conclusion This study provides initial insights into the epidemiology of dengue in Somaliland, though further research is needed to establish robust baseline data, highlighting its prevalence, particularly in urban adults. These preliminary findings suggest a potential need for enhanced surveillance and public health measures, pending confirmation from larger studies to address the emerging arboviral diseases in this region.